1999
DOI: 10.2355/isijinternational.39.553
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Fine Bubbles in Front of the Solidifying Interface.

Abstract: Experimental results were found to be well in accord with theoretical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 2 publications
1
35
0
Order By: Relevance
“…When the solute-build-up at the gap be- tween the advancing front and the particle causes the interfacial energy gradient around the particle, the attractive or the repulsive force operates the particle. 21) The concentration range where the interfacial energy remarkably decreases generally locates in the dilute concentration region (i.e. 0-0.2 at% for O and S in molten steel 31,32) ).…”
Section: Effect Of the Solutal Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the solute-build-up at the gap be- tween the advancing front and the particle causes the interfacial energy gradient around the particle, the attractive or the repulsive force operates the particle. 21) The concentration range where the interfacial energy remarkably decreases generally locates in the dilute concentration region (i.e. 0-0.2 at% for O and S in molten steel 31,32) ).…”
Section: Effect Of the Solutal Conditionmentioning
confidence: 99%
“…In addition to the two different forces, it was also reported that the concentration gradient ahead of the solidifying interface could promote movement of the inclusions in accordance with the solute concentration dependence of the interfacial energy. 21) Especially, the force due to the interfacial energy gradient may significantly affect the particle engulfment when a small amount of the solutes that are surface active is added. The proposed models of the particle pushing/engulfment [9][10][11][12][13][14][15][16][17][18][19][20] essentially consider the thermal and the solutal effects on the particle pushing/engulfment, but do not explicitly include the melt flow.…”
Section: Introductionmentioning
confidence: 99%
“…(7) and the velocity calculated from Eq. (5) of our paper 1) by taking into account possible experimental errors, respectively. According to Fig.…”
Section: Comparison Of Theoretical and Experimentalmentioning
confidence: 99%
“…Our paper named "Behavior of fine bubbles in front of the solidifying interface" 1) was published in ISIJ International (Vol. 39, 1999, p. 553).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is to attempt to give a better theoretical interpretation to the new and very precise experimental data obtained by Wang et al 1) The key equation in our new model is an improved equation on the force acting on a spherical particle or bubble moving towards a solidification front due to the existence of an interfacial energy gradient at the particle/liquid or bubble/liquid interface.…”
Section: Introductionmentioning
confidence: 99%